Analysis of Under-the-Table Child Adoption Practices in the Perspective of Islamic Law and Law No. 23 of 2002 Concerning Child Protection - Amaliah, Fitri; Sudrajat, Vickry Maulanna (CV. Strata Persada Academia, 2025)
The persistence of informal or under-the-table child adoption practices in Indonesia poses a significant challenge to the protection of children’s rights and legal certainty. Although adoption is formally regulated under statutory law and Islamic legal principles, informal arrangements remain prevalent, particularly in Sumber Subdistrict, where they are often conducted through verbal agreements without judicial authorization. This study aims to analyze the underlying factors contributing to such practices and to evaluate them from the perspectives of Islamic law and Law No. 23 of 2002 concerning Child Protection. Employing a qualitative normative juridical-descriptive method, this research draws upon primary legal sources, including statutory provisions, Qur’anic verses, Hadith, and fatwas, as well as secondary literature, and applies the Miles and Huberman model of qualitative analysis. The findings reveal that socio-cultural traditions, limited legal awareness, procedural complexity, and the perception of greater psychological security for children are the main drivers of informal adoption. From the standpoint of Islamic law, severing lineage (nasab) is strictly prohibited, while positive law considers such practices unlawful and subject to civil and criminal sanctions, particularly when involving data falsification or exploitation. The study concludes that harmonizing customary practices with statutory frameworks requires legal literacy initiatives, simplified adoption procedures, and stronger institutional coordination to ensure child protection while respecting social and cultural contexts.